1998
DOI: 10.1038/sj.leu.2401144
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary relapse after favorable molecular response to donor leukocyte infusions for recurring acute leukemia

Abstract: Donor leukocyte infusions (DLI) have turned out to be an efficient way to re-establish complete remission (CR) in chronic myeloid leukemia (CML) patients relapsing after allogeneic bone marrow transplantation (BMT). In these patients, absence of PCR bcr-abl fusion transcripts confirmed the potency of donor leukocytes to induce molecular response in relapsed CML. This ensured sustained remission and long-term survival. In this study, the capacity of DLI to induce molecular remission in acute leukemia relapse af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…50,51 These interventions may be combined with adjuvant therapy and/or supportive chemotherapy to prevent relapses in immuneprivileged sites. 52 …”
Section: Discussionmentioning
confidence: 99%
“…50,51 These interventions may be combined with adjuvant therapy and/or supportive chemotherapy to prevent relapses in immuneprivileged sites. 52 …”
Section: Discussionmentioning
confidence: 99%
“…9,10 In contrast, DLI for relapsed ALL has been much less effective. Although there have been many case reports showing that patients with ALL respond to DLI, [11][12][13][14][15][16][17][18][19] analyses of larger patient groups in multicenter registry studies have shown that DLI alone has limited efficacy in ALL, with one of 12 patients in the European registry study 20 and two of 15 in the North American registry study 21 reported to achieve CR with DLI alone. In the Japanese registry study, DLI alone induced CR in six of 24 patients, but only one patient maintained CR for 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Three patients have been reported with EM relapse while in sustained marrow remission following DLI for myeloid leukaemia relapsing post alloBMT, two of whom had significant GVHD. 15,17 Zomas et al 18 reported a patient with plasmacytomata which persisted despite DLI inducing marrow remission. Against the concept of site-dependent graftversus-tumour effects, however, are reports of EM relapse of acute leukaemia responding to DLI.…”
Section: Discussionmentioning
confidence: 99%